Amenemope: on the use of time, by Molefi Kete Asante - Carmo, Aline Cristina Oliveira de (2019)
In this text, Molefi Kete Asante presents Amenemope as an important representative of ancient Egyptian ethical philosophy, for his ability to combine elements of the cosmogony of his people, expressing the development of a humanism founded on the Egyptian way of life. In this text, three chapters of the Instructions of Amenemope, known as Seboyet, generally dated from the 10th century, are highlighted.